2020 Physics Education Research Conference Proceedings 2020
DOI: 10.1119/perc.2020.pr.white
|View full text |Cite
|
Sign up to set email alerts
|

Student evaluation of more or better experimental data in classical and quantum mechanics

Abstract: Prior research has shown that physics students often think about experimental procedures and data analysis very differently from experts. One key framework for analyzing student thinking has found that student thinking is more point-like, putting emphasis on the results of a single experimental trial, whereas set-like thinking relies on the results of many trials. Recent work, however, has found that students rarely fall into one of these two extremes, which may be a limitation of how student thinking is evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Compared with introductory physics courses, quantum mechanics is often considered to be very mathematical [22][23][24], counter-intuitive [25,26], and difficult to relate to the real world [27,28]. Although these characteristics may be true of other concepts covered in beyond-first-year lab experiments, prior work studying students in theoretical quantum mechanics courses has found that students' epistemological beliefs [28] and views about measurement uncertainty [29][30][31] vary between quantum and classical physics contexts. It is therefore important to understand what students are learning from quantum labs and what resources are necessary to achieve those goals, so they can be accomplished as equitably as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with introductory physics courses, quantum mechanics is often considered to be very mathematical [22][23][24], counter-intuitive [25,26], and difficult to relate to the real world [27,28]. Although these characteristics may be true of other concepts covered in beyond-first-year lab experiments, prior work studying students in theoretical quantum mechanics courses has found that students' epistemological beliefs [28] and views about measurement uncertainty [29][30][31] vary between quantum and classical physics contexts. It is therefore important to understand what students are learning from quantum labs and what resources are necessary to achieve those goals, so they can be accomplished as equitably as possible.…”
Section: Introductionmentioning
confidence: 99%